2016
DOI: 10.1038/srep38560
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve UCC2003 metabolises the human milk oligosaccharides lacto-N-tetraose and lacto-N-neo-tetraose through overlapping, yet distinct pathways

Abstract: In this study, we demonstrate that the prototype B. breve strain UCC2003 possesses specific metabolic pathways for the utilisation of lacto-N-tetraose (LNT) and lacto-N-neotetraose (LNnT), which represent the central moieties of Type I and Type II human milk oligosaccharides (HMOs), respectively. Using a combination of experimental approaches, the enzymatic machinery involved in the metabolism of LNT and LNnT was identified and characterised. Homologs of the key genetic loci involved in the utilisation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
152
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 78 publications
10
152
0
Order By: Relevance
“…Newer studies examined the ability of select Bifidobacterium breve strains to utilize HMOs (Ruiz-Moyano et al 2013, James et al 2016). Comparative genomics of B. breve shows that this species contains clusters related to HMO utilization, including those related to sialic acid, fucose, and LNB (Bottacini et al 2014).…”
Section: Molecular Mechanisms Of Utilization Of Human Milk Oligosacchmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer studies examined the ability of select Bifidobacterium breve strains to utilize HMOs (Ruiz-Moyano et al 2013, James et al 2016). Comparative genomics of B. breve shows that this species contains clusters related to HMO utilization, including those related to sialic acid, fucose, and LNB (Bottacini et al 2014).…”
Section: Molecular Mechanisms Of Utilization Of Human Milk Oligosacchmentioning
confidence: 99%
“…B. breve exhibits strain-specific growth on HMOs; however, most strains grow well on LNT (Ruiz-Moyano et al 2013). James et al (2016) used transcriptome analysis and functional studies to examine pathways involved in LNT and LNnT utilization by B. breve UCC 2003. In this work, galactosidases and solute-binding proteins from B. breve UCC 2003 associated with type I and II HMO utilization were characterized, and this strain used separate pathways that have overlapping properties to metabolize LNT and LNnT (James et al 2016).…”
Section: Molecular Mechanisms Of Utilization Of Human Milk Oligosacchmentioning
confidence: 99%
“…A more recent study by James et al [26] showed that recombinant lntA protein of B. breve UCC2003 [a homologue of GL-BG (IntA, as illustrated in Fig. 5)] showed hydrolytic activity toward lacto-N-tetoraose (Galb1-3GlcNAcb1-3Galb1-4Glc), degrading it into galactose and triose Lacto-N-triose [26]. Therefore, we also investigated the b-galactosidase activity of GL-SBP1 from B. breve YIT 4014 T against LNT, LNB, lactose, 3¢-GL, 4¢-GL and 6¢-GL (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Our data agreed well with these notable publications; furthermore, we found that these genes were involved in 3¢-and 6¢-GL utilization, but not 4¢-GL utilization. A more recent study by James et al [26] showed that recombinant lntA protein of B. breve UCC2003 [a homologue of GL-BG (IntA, as illustrated in Fig. 5)] showed hydrolytic activity toward lacto-N-tetoraose (Galb1-3GlcNAcb1-3Galb1-4Glc), degrading it into galactose and triose Lacto-N-triose [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being the third most abundant solid component in breast milk after lactose (Lac) and lipids, HMOs have no nutritional value for infants because of their resistance to pancreatic digestion (Kunz et al, 2000;Urashima et al, 2012). Several groups, including our own, have found the gene sets coding for enzymes that degrade HMOs (Sela et al, 2008;Garrido et al, 2016;James et al, 2016;Katayama, 2016;Matsuki et al, 2016) and have shown that these genes are limited to the infant gut-associated bifidobacterial species among gut microbes (Ruiz-Moyano et al, 2013;Katayama, 2016;Thomson et al, 2017). These findings suggest that it is highly likely that HMOs serve as selective nutrients for bifidobacterial species.…”
Section: Introductionmentioning
confidence: 99%